An Education Intervention to Improve Awareness on Road Safety: A Study Among School Going Teenagers in Indore - Mahawar, Priyanka; Dixit, Sanjay; Khatri, A K; Rokade, Rahul; Bhurre, Rohit; Kirar, Sanjeev; Jain, Rohit; Jamliya, Sanjay (National Journal of Community Medicine, 2013)
Introduction: The rapid and unplanned urbanization in India along with rise in number of motor vehicles lead to an alarming increase in morbidity and mortality owing to road traffic accidents (RTA) over the past few decades. Most of the factors responsible for RTA and its fatal consequences are preventable. A comprehensive multipronged approach can mitigate most of them. Objective: Our objective to do this study is to assess the level of knowledge of basic traffic rule in school going children and increase their knowledge by 30%. Methods: We have conducted educational intervention study on basic traffic rule awareness on 159 school going children age group 16-18 of Bal Vinay Mandir Higher Secondary School over a period of 3 months. Their knowledge about basic traffic rules was assessed by pre and post questionnaire which included basic traffic rules from the motor vehicle act 1989 and basic traffic signs. Results: Total 21.4% of the student knew to slow down vehicle near a zebra crossing while after intervention the number increased to 75.5%. Only 23.3% of the student knew the use of low beam of light in night while after intervention the number increased to 67.3%. Conclusion: Knowledge level increased after intervention so regular reinforcement of rules certainly would help in increasing awareness and also help people follows them.